Proceedings of the 2017 11th Joint Meeting on Foundations of Software Engineering 2017
DOI: 10.1145/3106237.3106238
|View full text |Cite
|
Sign up to set email alerts
|

Using bad learners to find good configurations

Abstract: Finding the optimally performing con guration of a so ware system for a given se ing is o en challenging. Recent approaches address this challenge by learning performance models based on a sample set of con gurations. However, building an accurate performance model can be very expensive (and is o en infeasible in practice).e central insight of this paper is that exact performance values (e.g., the response time of a so ware system) are not required to rank con gurations and to identify the optimal one. As show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 25 publications
0
117
0
3
Order By: Relevance
“…A typical approach uses sensitivity analysis [29], where performance models are learned by measuring the performance of the system under a limited number of sampled configurations. While this approach is cheaper and more effective than manual exploration, it still incurs the expense of extensive data collection about the software [3], [4], [7], [8], [10], [12], [26], [27], [30]. This is undesirable since this data collection has to be repeated if ever the software is updated or the environment of the system changes abruptly.…”
Section: Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…A typical approach uses sensitivity analysis [29], where performance models are learned by measuring the performance of the system under a limited number of sampled configurations. While this approach is cheaper and more effective than manual exploration, it still incurs the expense of extensive data collection about the software [3], [4], [7], [8], [10], [12], [26], [27], [30]. This is undesirable since this data collection has to be repeated if ever the software is updated or the environment of the system changes abruptly.…”
Section: Motivationmentioning
confidence: 99%
“…It has recently been shown that exact measures like MMRE can be somewhat misleading to assess configurations [12], [27], [36].…”
Section: Evaluation Criterionmentioning
confidence: 99%
See 3 more Smart Citations